Penerapan Model Project Based Learning Berbantuan Peer Tutoring Pada Pembelajaran Konsep Dasar IPA untuk Meningkatkan 4Cs Skills Mahasiswa Pendidikan Guru Sekolah Dasar - Maryono Maryono; Hendra Budiono (Jurnal Gentala Pendidikan Dasar, 2019)
The purpose of this study is to describe the application of the project based learning model with peer tutoring on the learning of Basic Science Concepts to improve 4Cs skills of Elementary School Teacher Education Students. This research is a classroom action research by adopting Kemmis and Taggart's research steps consisting of planning, action, observation and reflection. The subject of the study was the second semester PGSD students with a total of 39 people. Data collection instruments in this study were observation sheets of the implementation of the PjBL model, critical thinking skills tests, communication assessment observation sheets, student collaboration observation sheets, and student creativity assessment observation sheets in producing herbarium products. The results showed an increase in 4Cs student skills. In the first cycle, 4Cs skills of students with an average percentage of 70.11%, high category. In the second cycle showed an increase with an average percentage of 76.01% in the high category. Based on the results of the study it can be concluded that the project based learning model assisted by peer tutoring can improve the 4Cs skills of PGSD Jambi University students.